In search of visible-light photoresponsive peptide nucleic acids (PNAs) for reversible control of DNA hybridization - Zhang, Lei; Linden, Greta; Vázquez, Olalla (Beilstein Journal of Organic Chemistry, 2019)
Photoswitchable oligonucleotides can determine specific biological outcomes by light-induced conformational changes. In particular, artificial probes activated by visible-light irradiation are highly desired in biological applications. Here, we report two novel types of visible-light photoswitchable peptide nucleic acids (PNAs) based on the molecular transducers: hemithioindigo and tetra-ortho-fluoroazobenzene. Our study reveals that the tetra-ortho-fluoroazobenzene–PNA conjugates have promising properties (fast reversible isomerization, exceptional thermal stability, high isomer conversions and sensitivity to visible-light irradiation) as reversible modulators to control oligonucleotide hybridization in biological contexts. Furthermore, we verified that this switchable modification delivers a slightly different hybridization behavior in the PNA. Thus, both melting experiments and strand-displacement assays showed that in all the cases the trans-isomer is the one with superior binding affinities. Alternative versions, inspired by our first compounds here reported, may find applications in different fields such as chemical biology, nanotechnology and materials science.
Keywords: azobenzene; hemithioindigo; peptide nucleic acid (PNA); photoswitch; visible-light irradiation

(untitled) - Lubbe, A. S.; Szymanski, W.; Feringa, B. L. (Chem. Soc. Rev., 2017)

(untitled) - Ando, H.; Furuta, T.; Tsien, R. Y.; Okamoto, H. (Nat. Genet., 2001)

(untitled) - Monroe, W. T.; McQuain, M. M.; Chang, M. S.; Alexander, J. S.; Haselton, F. R. (J. Biol. Chem., 1999)

(untitled) - Shi, Y.; Koh, J. T. (ChemBioChem, 2004)

(untitled) - Shimizu-Sato, S.; Huq, E.; Tepperman, J. M.; Quail, P. H. (Nat. Biotechnol., 2002)

(untitled) - Tang, X.; Dmochowski, I. J. (Mol. BioSyst., 2007)

(untitled) - Mayer, G.; Heckel, A. (Angew. Chem., Int. Ed., 2006)

(untitled) - Li, L.; Tong, R.; Chu, H.; Wang, W.; Langer, R.; Kohane, D. S. (Proc. Natl. Acad. Sci. U. S. A., 2014)

(untitled) - Wang, Y.; Wu, L.; Wang, P.; Lv, C.; Yang, Z.; Tang, X. (Nucleic Acids Res., 2012)

(untitled) - Lucas, T.; Schäfer, F.; Müller, P.; Eming, S. A.; Heckel, A.; Dimmeler, S. (Nat. Commun., 2017)

(untitled) - Deiters, A.; Garner, R. A.; Lusic, H.; Govan, J. M.; Dush, M.; Nascone-Yoder, N. M.; Yoder, J. A. (J. Am. Chem. Soc., 2010)

(untitled) - Yamazoe, S.; Liu, Q.; McQuade, L. E.; Deiters, A.; Chen, J. K. (Angew. Chem., Int. Ed., 2014)

(untitled) - Shen, X.; Corey, D. R. (Nucleic Acids Res., 2018)

(untitled) - Lerch, M. M.; Hansen, M. J.; van Dam, G. M.; Szymanski, W.; Feringa, B. L. (Angew. Chem., Int. Ed., 2016)

(untitled) - Hüll, K.; Morstein, J.; Trauner, D. (Chem. Rev., 2018)

(untitled) - Asanuma, H.; Ito, T.; Yoshida, T.; Liang, X.; Komiyama, M. (Angew. Chem., Int. Ed., 1999)

(untitled) - Ito, H.; Liang, X.; Nishioka, H.; Asanuma, H. (Org. Biomol. Chem., 2010)

(untitled) - Schierling, B.; Noel, A.-J.; Wende, W.; Hien, L. T.; Volkov, E.; Kubareva, E.; Oretskaya, T.; Kokkinidis, M.; Rompp, A.; Spengler, B.; Pingoud, A. (Proc. Natl. Acad. Sci. U. S. A., 2010)

(untitled) - Zou, Y.; Chen, J.; Zhu, Z.; Lu, L.; Huang, Y.; Song, Y.; Zhang, H.; Kang, H.; Yang, C. J. (Chem. Commun., 2013)

(untitled) - Zhou, M.; Liang, X.; Mochizuki, T.; Asanuma, H. (Angew. Chem., Int. Ed., 2010)

(untitled) - Liu, M.; Asanuma, H.; Komiyama, M. (J. Am. Chem. Soc., 2006)

(untitled) - Asanuma, H.; Liang, X.; Nishioka, H.; Matsunaga, D.; Liu, M.; Komiyama, M. (Nat. Protoc., 2007)

(untitled) - Liang, X.; Wakuda, R.; Fujioka, K.; Asanuma, H. (FEBS J., 2010)

(untitled) - Kamiya, Y.; Takagi, T.; Ooi, H.; Ito, H.; Liang, X.; Asanuma, H. (ACS Synth. Biol., 2015)

(untitled) - Ogasawara, S.; Maeda, M. (Bioorg. Med. Chem. Lett., 2011)

(untitled) - Asanuma, H.; Ishikawa, T.; Yamano, Y.; Murayama, K.; Liang, X. (ChemPhotoChem, 2019)

(untitled) - Brieke, C.; Heckel, A. (Chem. – Eur. J., 2013)

(untitled) - Lewis, F. D.; Wu, Y.; Liu, X. (J. Am. Chem. Soc., 2002)

(untitled) - Cahová, H.; Jäschke, A. (Angew. Chem., Int. Ed., 2013)

(untitled) - Lubbe, A. S.; Liu, Q.; Smith, S. J.; de Vries, J. W.; Kistemaker, J. C. M.; de Vries, A. H.; Faustino, I.; Meng, Z.; Szymanski, W.; Herrmann, A.; Feringa, B. L. (J. Am. Chem. Soc., 2018)

(untitled) - Nielsen, P. E.; Egholm, M.; Berg, R. H.; Buchardt, O. (Science, 1991)

(untitled) - Janowski, B. A.; Kaihatsu, K.; Huffman, K. E.; Schwartz, J. C.; Ram, R.; Hardy, D.; Mendelson, C. R.; Corey, D. R. (Nat. Chem. Biol., 2005)

(untitled) - Mollegaard, N. E.; Buchardt, O.; Egholm, M.; Nielsen, P. E. (Proc. Natl. Acad. Sci. U. S. A., 1994)

(untitled) - Li, J.; Chen, M.; Zhang, H.; Liu, S.; Liu, J. (Chin. Sci. Bull., 2008)

(untitled) - Sawada, S.; Takao, T.; Kato, N.; Kaihatsu, K. (Molecules, 2017)

(untitled) - Stafforst, T.; Hilvert, D. (Angew. Chem., Int. Ed., 2010)

(untitled) - Albert, L.; Xu, J.; Wan, R.; Srinivasan, V.; Dou, Y.; Vázquez, O. (Chem. Sci., 2017)

(untitled) - Noonan, E. J.; Place, R. F.; Pookot, D.; Basak, S.; Whitson, J. M.; Hirata, H.; Giardina, C.; Dahiya, R. (Oncogene, 2009)

(untitled) - Ropero, S.; Esteller, M. (Mol. Oncol., 2007)

(untitled) - Ratilainen, T.; Holmén, A.; Tuite, E.; Haaima, G.; Christensen, L.; Nielsen, P. E.; Nordén, B. (Biochemistry, 1998)

(untitled) - Yue, S.; Li, J.; Zhang, J.; Lu, J.; Chen, M. (Chin. Sci. Bull., 2009)

(untitled) - Jarikote, D. V.; Köhler, O.; Socher, E.; Seitz, O. (Eur. J. Org. Chem., 2005)

(untitled) - Bléger, D.; Schwarz, J.; Brouwer, A. M.; Hecht, S. (J. Am. Chem. Soc., 2012)

(untitled) - Cordes, T.; Elsner, C.; Herzog, T. T.; Hoppmann, C.; Schadendorf, T.; Summerer, W.; Rück-Braun, K.; Zinth, W. (Chem. Phys., 2009)

(untitled) - Wiedbrauk, S.; Dube, H. (Tetrahedron Lett., 2015)

(untitled) - Knie, C.; Utecht, M.; Zhao, F.; Kulla, H.; Kovalenko, S.; Brouwer, A. M.; Saalfrank, P.; Hecht, S.; Bléger, D. (Chem. – Eur. J., 2014)

(untitled) - Albert, L.; Peñalver, A.; Djokovic, N.; Werel, L.; Hoffarth, M.; Ruzic, D.; Xu, J.; Essen, L.-O.; Nikolic, K.; Dou, Y.; Vázquez, O. (ChemBioChem, 2019)

(untitled) - Heinrich, B.; Bouazoune, K.; Wojcik, M.; Bakowsky, U.; Vázquez, O. (Org. Biomol. Chem., 2019)

(untitled) - Asanuma, H.; Liang, X.; Yoshida, T.; Komiyama, M. (ChemBioChem, 2001)

(untitled) - Borer, P. N.; Dengler, B.; Tinoco, I., Jr; Uhlenbeck, O. C. (J. Mol. Biol., 1974)

(untitled) - Wickstrom, E.; Choob, M.; Urtishak, K. A.; Tian, X.; Sternheim, N.; Talbot, S.; Archdeacon, J.; Efimov, V. A.; Farber, S. A. (J. Drug Targeting, 2004)

(untitled) - Nazarenko, I.; Pires, R.; Lowe, B.; Obaidy, M.; Rashtchian, A. (Nucleic Acids Res., 2002)

(untitled) - Zhang, D. Y.; Turberfield, A. J.; Yurke, B.; Winfree, E. (Science, 2007)